Association of sarcopenia and expression of interleukin-23 in colorectal cancer survival. Issue 10 (October 2021) - Hu, Wan-Hsiang; Chang, Ching-Di; Liu, Ting-Ting; Chen, Hong-Hwa; Hsiao, Chang-Chun; Kang, Hong-Yo; Chuang, Jiin-Haur
Summary: Background & aims: The relationship between sarcopenia and interleukin-23 (IL-23) has not been reported. We designed this study to investigate this relationship and the association of sarcopenia and interleukin-23 with poor prognosis of colorectal cancer. Methods: We used the %FINDCUT SAS macro to determine the cutpoints of the skeletal muscle index (SMI) to define sarcopenia in colorectal cancer patients. Immunohistochemical staining was performed to detect high and low IL-23 expression in cancer samples. Clinicopathological features were also recorded. The prognosis of the 5-year disease-free survival and overall survival were analyzed using univariate and multivariate methods. Results: A total of 114 patients with colorectal cancer were enrolled. The mean age was 63.2 years. Forty-six (40%) patients were female. Sarcopenia was defined as less than 50 cm 2 /m 2 for men and 32 cm 2 /m 2 for women and 52(46%) patients were defined as having sarcopenia. Sarcopenia was significantly associated with poor 5-year disease-free survival and overall survival ( p  = 0.003 and p  = 0.001, respectively). Multivariate adjustment demonstrated that sarcopenia was an independent predictor of the 5-year disease-free survival (hazard ratio = 1.827, p  = 0.024) and overall survival (hazard ratio = 3.669, p  < 0.001). A lower SMI was detected in patients with high IL-23 expression ( p  = 0.045). After grouping the patients with sarcopenia and IL-23 expression, the patients with sarcopenia and high IL-23 expression had the worst disease-free survival ( p  = 0.013) and overall survival ( p  = 0.007). Conclusions: This is the first study to explore the significant association between IL-23 expression and sarcopenia in colorectal cancer. Sarcopenia combined with IL-23, as an inflammatory marker, significantly predicted poor survival.